Music-based therapeutic interventions for medical school students with emotional regulation and mental health: a pre-post cohort study - Chen, Quan; Mao, Chaoqin; Qi, Laihua; Luo, Yang; Yang, Guangyao; Wang, Lei; Liu, Chen; Zheng, Chuansheng; Zhang, Jinxiang; Fan, Cheng (Frontiers in Psychology, 2024)
Purpose: Depression and anxiety are prevalent mental health challenges among college students. Music therapy has shown effectiveness in addressing depressive symptoms and enhancing psychosomatic functioning. This study aimed to evaluate the effectiveness of a 4-step structured music therapy program in improving mood and reducing symptoms of depression and anxiety among medical school students.The self-controlled study involved 45 medical school students (21 men and 24 women) aged 18-24 years to examine the prevalence of depression and anxiety, common mental health issues among medical school students. Participants underwent psychological assessment using the Symptom Checklist-90 (SCL-90), Self-Rating Anxiety Scale (SAS), and Self-Rating Depression Scale (SDS). An 8-week music therapy intervention, comprising four steps-sociality, interaction, music lessons, and creative expression-was administered.Results: Before-intervention, 55.6% and 15.6% students were identified as suffering from depression and anxiety respectively. Post-intervention, significant reductions in psychological distress, particularly in the Global Severity Index (GSI) and Positive Symptom Total (PST) on the SCL-90 scale, were observed (P < 0.05). Male students exhibited notable improvements in various psychological symptoms compared to females. Junior grade students demonstrated greater improvements, and clinical medicine students exhibited significant enhancements in specific areas post-intervention.The structured music therapy program showed promising results in improving mood and regulating emotions among medical school students. Music therapy holds potential as a holistic approach to address mental health challenges in this demographic.